Non-pharmacological treatment of Alzheimer’s disease: an update - Wang, Shaofen; Xu, Haochen; Liu, Guangdong; Chen, Limei (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder that significantly impairs memory, cognitive function, and the ability to perform daily tasks. The pathological features of AD include β-amyloid plaques, neurofibrillary tangles, and neuronal loss. Current AD treatments target pathological changes but often fail to noticeably slow disease progression and can cause severe complications, limiting their effectiveness. In addition to therapies targeting the core pathology of AD, a more comprehensive approach may be needed for its treatment. In recent years, non-pharmacological treatments such as physical therapy, exercise therapy, cell therapy, and nanoparticles have shown great potential in mitigating disease progression and alleviating clinical symptoms. This article reviews recent advances in non-pharmacological treatment approaches for AD, highlighting their contributions to AD management and facilitating the exploration of novel therapeutic strategies.